ВЕШТАЧКА ИНТЕЛИГЕНЦИЈА У ОБРАЗОВАЊУ: РЕГУЛАТОРНИ ОКВИРИ НА МЕЂУНАРОДНОМ, РЕГИОНАЛНОМ И НАЦИОНАЛНОМ НИВОУ - Ignjatovic, Gordana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
Abstract: This research paper explores the regulatory frameworks on AI technologies at the international, regional and national level, focusing on documents related to AI application in education. The first part provides an insight into the broad conceptual framework of Artificial Intelligence (AI) and AI-related terminology. The second part provides an overview of documents on AI adopted at the international level (OECD, UNESCO), regional level (EU, CoE) and national level (Serbia), with specific reference to key documents aimed at shaping the use of AI in education. The third part outlines the benefits/opportunities, drawbacks/challenges, concerns/risks and key considerations in the process of integrating AI in education. Based on the research findings, the paper points to the importance of a balanced, human-centered and pedagogy-driven integration of AI technologies, based on carefully designed regulatory framework in line with the highest ethical principles, pedagogical standards and guaranteed human rights. Relevant infrastructure, resources, support, guidelines, and practical training on AI literacy and competencies are essential for transparent, responsible and safe integration of AI in education.
Keywords: Artificial Intelligence; AI technologies; regulatory framework; ethical principles; education